PENDEDERAN IKAN BLACK MOLLY (POECILLIA SPHENOPS) DENGAN PEMBERIAN PAKAN TAMBAHAN CACING SUTRA DI INSTALASI BALAI BENIH IKAN LINGSAR: Black Molly Fish (Poecillia sphenops) Nursery Breeding With Silk Worm Additional Feeding at The Lingsar Fish Seed Center Installation - Ferli Armadani; Aminullah Aminullah (Al-Qalbu: Jurnal Pendidikan, Sosial dan Sains, 2026)
This research is important to understand and study the nursery techniques of black molly fish (Poecilia sphenops) with the supplemental feeding of silkworms at the Lingsar Fish Seed Center Installation. This research is a quasi-experimental study using observation, interviews, and documentation as data collection techniques. The experiment or trial conducted was the provision of silkworms as natural food to increase the growth of black molly fish. The results of the observations indicate that the nursery technique of black molly fish (Poecilia sphenops) with the supplemental feeding of silkworms includes: Aquarium or Nursery Container Preparation, Seed Distribution, Feed Management, Growth Observation, and Water Quality Management. Feeding with additional silkworms can increase weight from 0.34 grams to 1.58 grams, and length from 1.62 centimeters to 3.90 centimeters. Survival Rate (SR) of black molly fish raised at the Lingsar Fish Seed Center (BBI Lingsar) achieved a SR of 70%. This value was obtained from an initial total of 20 fish and a total of 14 fish at the end of the maintenance period. Water quality during observations with temperatures ranging between 24 °C - 27 °C and pH ranging between 7.0 - 8.0